Contextualizing a conceptual geriatric dentistry module for Malaysian dental undergraduate scenario /Jacob John Chiremel Chandy - Jacob John, Chiremel Chandy (2022)
The world is progressing into a vulnerable longevity revolution with the falling fertility rate and increased life expectancy. The elderly cohort suffer from multiple morbidities, increasing the burden on the curative, preventive, and promotive healthcare system. They are at risk of chronic diseases of the oral cavity, including root caries, periodontitis, tooth loss, benign mucosal lesions, and oral cancer. Oral health has close link with diet and nutrition and it may also affect the course and pathogenesis of systemic diseases. A competent general dental practitioner with appropriate geriatric dental education is a key healthcare provider in this complex system. Being adult learners, dental students should be able to apply their experiential learning knowledge and skills for their clinical judgement about their geriatric patient’s needs, concerns, or health problems, and/or the decision to act, use or modify standard approaches, or improvise new ones as deemed appropriate by the patient’s response. This study intends to contextualize a conceptual geriatric dentistry module appropriate for a competent graduate from all dental institutions in Malaysia. Twenty-four dental academics engaged in the teaching of subjects related to geriatric dentistry throughout the dental institutions in Malaysia were invited to participate in this online focus group discussion, with each group comprising of 6 to 8 participants. Ethical approval was obtained before commencement of the study. The researcher, cum moderator, prepared the interview protocol based on the research objective and a semi-structured questioning route to generate responses. All verbal interactions were captured via video and audio recording and note taking. The interview content was transcribed verbatim with care taken not to record names and locations, for further coding and systematic analysis of the discussion. Thematic analysis, using a deductive approach to identify codes and themes, was employed for data analysis. Sixteen (66% response rate) respondents from various dental disciplines and institutions participated in 2 separate FGD, each lasting nearly 120 minutes, upon achieving data saturation. The variation in the teaching of the subject was very evident. Four themes emerged for the teaching content namely public health issues, aging process, geriatric dental care, and patient centred care. The teaching delivery strategies also had 4 themes namely small group classroom sessions, clinical sessions, service learning and asynchronous learning strategies. The most appropriate learning environment for geriatric dentistry would include hospital and community settings in addition to the traditional dental clinic environment. Workplace based assessment would complement well the existing clinical competency and written examinations that are employed for assessment. Having identified these basic themes as the conceptual framework for an integrated geriatric dentistry module we can now contextualize it as part of andragogy whereby the students apply their accumulated experiential learning skills and clinical judgement in providing dental care for their geriatric patients from various categories of functionalities. The scope of this research needs to be explored further to include other stakeholders in the future. The inclusion of an integrated geriatric dentistry module in our dental curriculum should help improve the dental services for our aged population in the future.